The Effectiveness of University Administration in Iraq and Its Role in Promoting Institutional Reform - Atshsn, Nassrullah (Journal of Legal Sciences, 2025)
Universities derive their administrative structures and powers from Ministry Law No. (40) of 1988 and University Service Law No. (23) of 2008. The powers and administrative structures of universities and colleges are centralized, as defined by the Ministry Law and related regulations and instructions. These can only be altered by amendment from Parliament or by regulations or instructions from the Ministry. Universities and colleges cannot develop themselves except through new legislation, which may take years to enact or grant them the necessary powers. There are several obstacles that contribute to hindering the development of the administrative organization of universities and colleges in Iraq. Some of them are legislative, related to state policy, some are technical, related to the need to develop leadership and staff, and some are administrative and financial. As for the proposed solutions, it is necessary to address the legislation related to higher education, most importantly the Ministry of Higher Education Law of 1988, so that universities and colleges can develop themselves, expand, and decentralize their powers and work in a way that serves their administrative organization. The executive authorities must adhere to the legislation for establishing university institutions (universities, colleges, etc.), so that the establishment occurs after the completion of the requirements of infrastructure and funds. A high governmental committee should be formed, consisting of (higher education, planning, and finance), to inspect all universities, especially their administrative, financial, teaching, and infrastructure structures, and consequently hold accountable senior university leaders who are negligent in their work. In order to achieve administrative integration in universities, each university should be obligated to establish a center for strategic or international studies and research after fulfilling its requirements, or advanced scientific and administrative centers that help the university reach regional and global levels on the one hand, and help the university obtain a good financial resource through innovations and patents. Finally, it is necessary to establish a council concerned with universities called the (Council for Regulating Iraqi Universities), which consists of all official government universities in addition to a representative of private universities. Its goal is to develop practical and implementable plans for developing universities administratively, academically and financially, in addition to providing consultations to the government before issuing decisions to establish new universities or colleges in order to maintain the quality of higher education in Iraq and the ability to compete with regional and global universities.